ACTIVITY OF BACTERIAL ANTIBIOTICS AGAINST SOME PATHOGENIC BACTERIA ISOLATED FROM CALVES DIARRHOEA IN BAGHDAD (part I) - & Ibrahim, Abdulridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was aimed to isolate, identify and characterize the bacterial pathogens causing calf diarrhea in Baghdad province and study it's susceptibility toward different antibiotics. The study was conducted on 105 faecal samples collected directly from the rectum of diarrhoeic calves and brought to the laboratory for bacteriological examination. Isolation and identification of the microorganisms were confirmed on the basis of their, staining, cultural, morphology and biochemical tests. Furthermore, antibacterial test was study for different clinical isolates of pathogenic bacteria toward varying concentration of antibiotics by disc diffusion technique. samples were examined for the isolation of bacteria of which 45 (42.85%) samples were positive for E. coli, 22 (20.95%) samples were positive for Salmonella spp, 16 (15.23%) samples were positive for Staphylococcus, 12 (10.5%) samples were positive for Mixed infection, 10 (9.52%) samples were negative for bacteria. The susceptibility study revealed that most of the E. coli, Salmonella spp., and Staphylococcus spp. were resistant to ampicillin, amoxicillin, erythromycin, gentamicin, tetracycline, streptomycin and trimethoprim / sulfamethoxazole with varying percentages, and susceptible to ciprofloxacin and azithromycin. The findings of the present study indicate that the clinical isolates of pathogenic bacteria resistance to  a number of bacterial antibiotics.